Predicting policy: exploring news attention to policy issues in electoral debates. Issue 5 (20th October 2017) - Turcotte, Jason
ABSTRACT: Despite news fragmentation, declining levels of voter knowledge, and waning interest in U.S. politics, debates attract mass audiences, reduce barriers of learning, and offer a greater focus on policy issues than that typically found in campaign news coverage. Nonetheless, debates are routinely driven by the same commercial, for-profit news journalists who routinely emphasize strategic campaign issues (e.g. the horserace) at the expense of policy content. As moderators, journalists have been scrutinized for the agenda they set in electoral debates. Using a multiyear dataset that treats debate questions as the unit of analysis, this quantitative content analysis explores news routines in the context of mediated debates while isolating media characteristics predictive of news attention to policy matters. The data show that journalists working for local news outlets and those working for commercial outlets are more likely to emphasize policy issues. Implications for debate sponsorship and campaigns are discussed.